Later is better: mobile phone ownership and child academic development, evidence from a longitudinal study. Issue 8 (17th November 2019) - Dempsey, Seraphim; Lyons, Seán; McCoy, Selina
ABSTRACT: Digital technologies have become an increasingly prominent feature of children's lives both within and outside educational environments (McCoy, Quail, and Smyth 2012. Influences on 9-Year-Olds' Learning: Home, School and Community . Dublin: Department of Children and Youth Affairs). Despite considerable media debate, we have little robust evidence on the impact of technology use on children's development, both academically and socially. Much of the literature in this area relies on small-scale cross-sectional studies. Using longitudinal data on 8500 9-year-old children in Ireland, we examine the influence of early mobile phone ownership on children's performance in reading and maths between 9 and 13 years of age. Across both reading and maths domains, children who already report owning a phone by the age of nine fare less well in terms of their academic development as they move into adolescence. The measured effects are sizeable, implying about 4 percentile lower ranking on standardised tests for an average student. Our results are consistent with the idea that there may be significant educational costs arising from early mobile phone use by children. Parents and policymakers should consider whether the benefits of phone availability for children are sufficiently large to justify such costs. We suggest a range of direct and indirect cognitive effects that could help explain these results.